Birth outcomes of cases with right sided obstructive defects of heart a population-based case-control study - Vereczkey, Attila; Kósa, Zsolt; Csáky-Szunyogh, Melinda; Urbán, Róbert; Czeizel, Andrew (International Journal of Health, 2013)
Background: Among structural birth defects, i.e. congenital abnormalities, the most common group includes congenital heart defects (CHDs), however, the underlying causes are unclear in the vast majority of cases with CHD.Objectives: Cases with different CHD-entities as homogeneously as possible are planned to evaluate. Thus the medically recorded birth outcomes of lethal or surgically corrected cases with different groups of right sided obstructive defects of heart (RSODH) were evaluated.Method: The population-based large dataset of the Hungarian Case-Control Surveillance of Congenital Abnormalities was used and date were analyzed between 1980-1996, including 200 live-born cases with isolated RSODH, 72, 13,7 and 108 had congenital stenosis of pulmonary valve, atresia/stenosis of tricuspid valve, Ebsteins anomaly, and atresia/stenosis of pulmonary artery, respectively compared to 304 matched controls and 38,151 population controls without any defects.Results: A higher rate of preterm birth and low birthweight was found in cases with RSODH born in somewhat elder women with higher birth order and lower socioeconomic status. However, 4 groups of RSODH were different from epidemiological aspect, and the degree of intrauterine growth restriction depended on the group of RSODH and the sex of fetuses.Conclusions: The pathogenesis-oriented classification of RSODH is not associated with similar epidemiological birth outcomes of cases with different RSODH groups.